2021
DOI: 10.3389/fonc.2021.724415
|View full text |Cite
|
Sign up to set email alerts
|

circRPS16 Promotes Proliferation and Invasion of Hepatocellular Carcinoma by Sponging miR-876-5p to Upregulate SPINK1

Abstract: The roles of serine protease inhibitor Kazal type 1 (SPINK1) in multiple types of cancers have been significantly documented. However, its specific roles in hepatocellular carcinoma (HCC) remain to be investigated. This study found that SPINK1 is upregulated in HCC and its upregulation correlates with poor prognosis. Besides, functional assays revealed that SPINK1 promotes cell proliferation, cell cycle, and invasion in vitro. Through bioinformatics analysis, we speculate that circRPS16 regulates SPINK1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…circRNAs retained in the cytoplasm act as miRNA sponges to regulate the expression of miRNA target genes (51). Lin et al (52) showed that circRPS16 acts as a miR-876-5p sponge to regulate the expression of SPINK1 in HCC. In HCC, miR-876-5p acts as the target of lncRNA PITPNA-AS1, long noncoding RNA SNHG14 and LINC-ROR, thereby regulating HCC proliferation and sorafenib sensitivity (53).…”
Section: Spink1 Is Regulated By Mirnamentioning
confidence: 99%
“…circRNAs retained in the cytoplasm act as miRNA sponges to regulate the expression of miRNA target genes (51). Lin et al (52) showed that circRPS16 acts as a miR-876-5p sponge to regulate the expression of SPINK1 in HCC. In HCC, miR-876-5p acts as the target of lncRNA PITPNA-AS1, long noncoding RNA SNHG14 and LINC-ROR, thereby regulating HCC proliferation and sorafenib sensitivity (53).…”
Section: Spink1 Is Regulated By Mirnamentioning
confidence: 99%
“…( Ueno et al, 2014;Shibasaki et al, 2015) SPINK1 Promoting HCC cell proliferation, cell cycle, and invasion in vitro (Huang et al, 2021;Lin et al, 2021) Downregulating E-cadherin and inducing EMT of HCC to promote metastasis Ying et al (2017) It could be regarded as a potential biomarker for early detection and targeted therapy of HCC. (Marshall et al, 2013;Li et al, 2015;Jia et al, 2022) It was a downstream effector of the CDH17/β-catenin axis in HCC.…”
Section: Mt1mmentioning
confidence: 99%